Religiousness as a human strength - José David Urchaga-Litago; Consuelo Morán-Astorga; María José Fínez-Silva (INFAD, 2019)
Multiple investigations show that religiosity is a factor of physical and psychological health. A review of these studies is presented and the results are interpreted. Religious people have less depression, anxiety, stress, suicide, and less unhealthy habits such as alcohol and other psychoactive substances. Religious people have lower rates of morbidity and mortality, presenting better and faster recoveries in physical diseases (such as cardiac surgery or hip surgery), in addictions (alcohol and other substances), or in post-traumatic stress. These evidences can be related to different psychological strengths that religiosity promotes, in a special way with forgiveness, gratitude, spirituality, justice, hope, humanity and the strengthening of interpersonal relationships.